RIBONUCLEIC ACID SYNTHESIS DURING MITOSIS AND MEIOSIS IN THE MOUSE TESTIS - Monesi, Valerio (The Rockefeller University Press, 1964)
The pattern of ribonucleic acid synthesis during germ cell development, from the stem cell to the mature spermatid, was studied in the mouse testis, by using uridine-H(3) or cytidine-H(3) labeling and autoradiography. Incorporation of tritiated precursors into the RNA occurs in spermatogonia, resting primary spermatocytes (RPS), throughout the second half of pachytene stage up to early diplotene, and in the Sertoli cells. Cells in leptotene, zygotene, and in the first half of pachytene stage do not synthesize RNA. No RNA synthesis was detected in meiotic stages later than diplotene, with the exception of a very low rate of incorporation in a fraction of secondary spermatocytes and very early spermatids. At long intervals after administration of the tracer, as labeled cells develop to more mature stages, late stages of spermatogenesis also become labeled. The last structures to become labeled are the residual bodies of Regaud. Thus, the RNA synthesized during the active meiotic stages is partially retained within the cell during further development. The rate of RNA synthesis declines gradually with the maturation from type A to intermediate to type B spermatogonia and to resting primary spermatocytes. "Dormant" type A spermatogonia synthesize little or no RNA. The incorporation of RNA precursors occurs exclusively within the nucleus: at later postinjection intervals the cytoplasm also becomes labeled. In spermatogonia all mitotic stages, except metaphase and anaphase, were shown to incorporate uridine-H(3). RNA synthesis is then a continuous process throughout the cell division cycle in spermatogonia (generation time about 30 hours), and stops only for a very short interval (1 hour) during metaphase and anaphase.